Comparison of various aspects of women's lives between infertile and women with and without tubal ligation: a comparative cross-sectional study - Mahnaz Ashrafi; Shahideh Jahanian Sadatmahalleh; Negin Mirzaei; Nadia Jahangiri; Samaneh Youseflu; Malihe Nasiri (BMC, 2021)
Abstract Background The aim of this study is to compare anxiety, depression, body image, self-esteem, sexual function, and quality of life (QoL) between infertile women and control fertile women undergoing tubal ligation (TL) and using condom. Methods This cross-sectional study was conducted on 600 women in three groups of infertile and control fertile women with or without TL (200 women in each group), who met the inclusion criteria. They were selected from Royan Institute and a number of health care centers in Tehran (Iran) from May 2017 to February 2019. The subjects were asked to fill out the Short Form Health Survey (SF-12), Female Sexual Function Index (FSFI), Hospital Anxiety and Depression Scale (HADS), Body Image Concern Inventory (BICI), and Rosenberg' Self-Esteem Scale (RSES). One-way ANOVA was used to identify the possible statistical differences between the three groups of participants. Results The mean scores of all FSFI domains were lower in the control TL women, and the differences between the three groups in all dimensions were statistically significant. In addition, the TL group had more female sexual dysfunction (FSD) comparing to the infertile and condom group (22.43 ± 5.30, 24.79 ± 4.74, and 28.03 ± 3.29, respectively P <  0.001). There was a significant difference between the three groups in SF-12 scores (76.59 ± 13.14, 68.49 ± 14.47, and 78.87 ± 12.62, respectively P < 0.001). Also there was a significant difference between the three groups in anxiety, depression, and total scores of HADS (P  < 0.001). Furthermore, infertile women had lower body image (P  < 0.05) and the TL group had lower self-esteem comparing to the two other groups (P  < 0.05). Conclusions The findings revealed the adverse effects of using TL on the anxiety, depression, sexual life, body image, and QoL of women. It is recommended that health-care professionals should increase their awareness and knowledge regarding the side-effects of using TL on women's lives and share this information with the patients.